Brain Atrophy Rates for Stable Multiple Sclerosis Patients on Long-Term Fingolimod versus Glatiramer Acetate - Honce, Justin M.; Nair, Kavita V.; Hoyt, Brian D.; Seale, Rebecca A.; Sillau, Stefan; Engebretson, Eric; Schurr, Brittany; Corboy, John R.; Vollmer, Timothy L.; Alvarez, Enrique (Frontiers in Neurology, 2020)
Background: Clinically stable multiple sclerosis (MS) patients on long-term therapy often have negligible acute inflammation on MRI. Brain atrophy may provide insight into subclinical disease progression in such populations. Objective: This study aims to compare brain atrophy for age- and gender-matched MS patients treated for >2 years with fingolimod (FTY) or glatiramer acetate (GA), examining brain volume, cognition, and patient-reported outcomes (PROs). Methods: Stable relapsing-MS patients, age 18–60, on FTY or GA for >2 years were followed up for 2 years. MRI brain and lesion volumes, cognitive measures, and PROs were collected at baseline and annually. Results: Forty-four FTY and forty-three GA patients completed baseline and year 2 visits. No differences in age, gender, or education were observed. Median EDSS was 2.0GA and 2.5FTY (p = 0.22). Treatment duration was longer for GA, 6.50GA vs. 3.73FTY years (p < 0.001). Baseline geometric mean T2LV were different, GA = 1,009.29 cm3 vs. FTY = 2,404.67 cm3 (p = 0.0071). Baseline brain volumes were similar, GA = 1,508 cm3 vs. FTY = 1,489 cm3 (p = 0.2381). Annualized atrophy rates, adjusted for baseline and at mean baseline value, were GA = −0.2775% vs. FTY = −0.2967% (p = 0.7979). No differences in cognitive measures or PROs were observed. Conclusions: Stable MS patients on long-term treatment with FTY and GA have similar brain volume loss rates. Differences in baseline disease severity may suggest patients with more aggressive disease treated with FTY may achieve similar brain volume loss rates as patients with milder baseline disease on GA.